Ghar Mein Kām Hai (There is Work in the House): When Female Factory Workers become 'Coopted Domestic Labour'. (August 2018) - Chambers, Thomas; Ansari, Ayesha
This article examines the utilization of female Muslim factory workers, in a North Indian woodworking industry, as domestic labour in the homes of their employers. The ethnography illustrates the importance of considering hidden forms of domestic-sector employment where workers are coopted into domestic tasks. The illumination of 'coopted domestic labour' has implications for understanding the breadth and scope of the sector and contributes to debates around its regulation, definition, growth and feminization. Female Muslim factory workers did not see 'coopted domestic labour' as a livelihood 'choice' but as exploitation enabled through employers' tactics, such as the use of advance payments, forms of 'neo-bondage', and through structural continuity across domestic and industrial contexts which situated women at the bottom of the labour hierarchy. It also involved complex negotiations around reputation, character and practices of purdah (veiling) which, whilst already an issue for those working in factories, became intensified when entering the homes of others. The article develops its contribution by introducing the category of 'coopted domestic labour' and empirically illustrating its intersection with gender norms, Islam, forms of neo-bondage and structural considerations.